Displaying emotion via dynamic use of address terms in Chinese family conflict talk - Gao, Jun; Ma, Lirong (East Asian Pragmatics, 2023)
This paper investigates the dynamic use of address terms in accordance with the emotional state of the speaker. Analyses of data from three Chinese TV dramas about family life revealed that Chinese family conflict talk was characterised by a predominant use of full name and kinship term address. Moreover, two distinct patterns emerged regarding the use of address terms across the three conflict phases: A. (familiarised) given name/kinship term/no address – full name – full name/no address, and B. (familiarised) given name/kinship term/no address – (familiarised) given name/kinship term – (familiarised) given name/kinship term/no address. Further analysis demonstrated that this dynamic use of address terms was associated with the emotional state of the speaker. This study contributes to research on family life by shedding light on the ways in which participants use address terms dynamically in conflictual settings and at the same time on the ways in which address terms are embedded in such potentially aggravating and emotionally charged social actions.